Lateglacial-Holocene abrupt vegetation changes at Lago Trifoglietti in Calabria, Southern Italy: The setting of ecosystems in a refugial zone - Beaulieu, Jacques-Louis de; Wulf, Sabine (Quaternary science reviews, 2017)
Retrospective science such as palaeoecology deeply depends on the preservation of archives in sensitive places. As an example, mountains of medium altitude from Mediterranean peninsulas have long been identiﬁed by biogeographers as refuges zones allowing the survival of European temperate taxa during the ice ages, but archives to validate this hypothesis are scarce, especially in Southern Italy. Here we present a new sequence from Lago Trifoglietti (1048 m a.s.l.) in the Calabrian Mountains, which covers the Late Glacial Interstadial (LGI, corresponding to the Bo€lling-Allero€d period in northern-central Europe) and the transition to the Holocene. The independent chronology based on seven radiocarbon dates is supported by the evidence of three tephra layers already identiﬁed in other regional sequences. During the LGI, besides the high diversity of non arboreal pollen grains, a great number of pollens of temperate forest trees are present or abundant (mostly deciduous oaks and ﬁr). These assemblages suggest that the site was above but not far from the upper limit of diversiﬁed woodland stands. They conﬁrm a local survival during the last glacial. The Younger Dryas is not marked by major changes, and oak percentages are even higher, suggesting a resilient expansion at lower altitude. Surprisingly the site remains above the timberline until an aridity crisis centered at 11,100 cal 14C yr PB, which is correlated with the Preboreal Oscillation (PBO). This event is immediately followed by the local settlement of a dense ﬁr and beech forest around the lake. A comparison with other Italian key sequences aims at explaining the climate forcing factors that governed this original vegetation dynamic. Further investigations using additional proxies are needed for a more robust climate reconstruction.
Available online 12 January 2017
Gesehen am 20.08.2018